Pengembangan UMKM Melalui Program Desain Kemasan, dan Metode Pemasaran Produk Karak Kaliang Talua dan Roti Kariang dengan Pemanfaatan Sosial Media Instagram - Nilda Tri Putri; Muhammad Erlangga Adi Nugraha; Adisty Luthfiah; M. Alif Arrahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The community engagement aims to empower Micro, Small and Medium Enterprises (MSMEs) through implementing strategies for packaging designs and marketing using Instagram social media. The case studied was Karak Kaliang Talua RF UMKM in Nagari Sianok Anam Suku, which faced challenges in branding and marketing. The problem-solving proposed involves creating new logos stickers and improving packaging quality to increase product value, as well as setting up a social media Instagram account for digital promotion. The implementation stages involved an initial survey, discussions with MSME owners, and submission of results in logo designs and stickers. The results included promotional videos, Instagram accounts, and created email accounts. In its implementation, this program overcame the problems faced by MSME Karak Kaliang Talua RF. The updated logo, sticker and packaging designs have had a positive impact on the product image, increasing consumer appeal. Using Instagram social media as a marketing tool opens up opportunities for market expansion and reaching consumers outside the local area.